Optimalisasi teknologi informasi dan komunikasi untuk meningkatkan kualitas tata kelola madrasah aliyah di era digital - Sholikah, Maratus (Maliki Interdisciplinary Journal, 2024)
This research aims to examine strategies for improving the quality of Madrasah Aliyah management in the digital era through the application of information and communication technology (ICT). Technological developments require Madrasah Aliyah to adapt and utilize ICT to increase management effectiveness and efficiency. However, ICT implementation still faces various challenges. The method used is literature study by analyzing various relevant sources. The results of the study show three main strategies: 1) development of an integrated madrasah management information system; 2) increasing ICT competency of human resources; and 3) strengthening ICT governance. The implementation of this strategy is expected to improve the quality of education services, increase stakeholder participation, and strengthen the competitiveness of madrasas. Successful implementation requires policy support, resource allocation, and commitment from all madrasa components to carry out digital transformation in a gradual and planned manner.